Understanding EFL Students’ Cognitive and Linguistic Challenges and Their Coping Strategies in Thesis Proposal Writing (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aimed to identify the cognitive and linguistic challenges EFL undergraduate students face in writing thesis proposals and to explore the coping strategies they employ. Method: A mixed-methods approach with a dominant descriptive quantitative design was utilized. Data were collected from 32 EFL students via a Likert-scale questionnaire and semi-structured interviews with five purposively selected students based on their proposal stages (pre- or post-seminar). Quantitative data were analyzed using descriptive statistics (percentages), and qualitative data were analyzed through content analysis. Results: The findings revealed cognitive challenges in topic selection (37.5% neutral), literature review (50.1% struggled to find sources), and research methodology (53.1% faced difficulties). Linguistic difficulties included grammar accuracy (56.3% struggled), vocabulary choice (46.9% found challenging), and coherence (56.3% neutral on logical flow). Coping strategies included peer discussions (59.4% effective), supervisor consultations (68.8% helpful), extensive reading (62.5% useful), and time management (50% planned effectively). A significant portion of neutral responses (up to 56.3%) indicated uncertainty in self-assessment. Novelty: This research highlights neutral responses as indicators of cognitive hesitation, offering insights through mixed-methods integration. It recommends structured academic support, such as methodological workshops and language training, to improve thesis proposal writing in Indonesian higher education.